(untitled) (Research, Society and Development, 2021)
Several biomarker enzymes such as catalase (CAT) and glutathione S-transferase (GST) can be used to measure oxidative stress in animals caused by exposure to xenobiotics. The objective of the present study was to characterize different points of the Capivari (CP1 and CP2), Paraguaçu (PG1 and PG2) and Subaé (SB1 and SB2) Rivers, state of Bahia, in relation to the presence of xenobiotics, using CAT and GST as bioindicators in M. jelskii. The water-sampling sites were considered urban or rural and in all of them signs of environmental degradation were observed. Therefore, acute exposure tests (96h) were performed with water samples collected during the dry and rainy seasons. Results showed that the activity of CAT and GST in prawns exposed to water from CP1 and CP2 were very similar, while those exposed to water from PG1, PG2, SB1 and SB2 formed distinct groups of data. Significant increase in the activity of at least one of the analyzed enzymes in each sampling site was observed, when compared to animals in the control group. This demonstrated a possible oxidative stress in M. jelskii caused by the presence of xenobiotics in the water (e.g., domestic sewage, pesticides, oil, and heavy metals). Enzymatic activities were higher in animals from experiments carried out in the rainy season, except for the CAT activity of animals exposed to water from Subaé River. This study demonstrated the potential of M. jelskii as bioindicator and contributed to the knowledge of aspects of the antioxidant defense system of this species.